Observing the Etiquettes of Visiting the Blessed Court of the Prophet (PBUH): An Analytical Study of Contemporary Practices - Qazi Raza Ahmed Qureshi; Dr. Mohsin Zia Qazi (Journal of Religion and Society, 2026)
The central focus of Islam’s beliefs, intellectual framework, and ethical system is the person of the Prophet Muhammadﷺ. The Prophet’sﷺ sacred personality is not merely a historical or spiritual figure; rather, it represents the practical manifestation of divine revelation, the exposition of Shariah, and the foundation of Islamic civilization. Accordingly, the Qur’an and Sunnah emphasize that one’s relationship with the Prophet ﷺ must be governed by exceptional respect, reverence, and decorum. Attendance at the Prophet’s ﷺ presence whether through the physical visitation of his sacred shrine or through spiritual engagement via remembrance, salutations, and adherence to his exemplary life is considered a profound blessing. However, the benefit and acceptance of such engagement are contingent upon observing the proper etiquette of the Prophet ﷺ. The significance of this etiquette is underscored by the Qur’anic injunctions that forbid raising one’s voice, asserting precedence, or acting carelessly in the Prophet’s ﷺ presence, linking such behaviour to a spiritual and moral risk for faith. Prophetic traditions (Ahadith), the practices of the Companions (Sahabah), jurisprudential scholarship, and the teachings of Sufi masters consistently affirm that respect for the Prophet ﷺ is not limited to outward gestures; it entails heartfelt reverence, thoughtful reflection, and practical adherence to his guidance. This etiquette is thus both a marker of faith, a prerequisite for the acceptance of deeds, and a foundation for spiritual development. In the contemporary era, as religious consciousness increasingly becomes limited to formal or emotional expressions, the concept of etiquette toward the Prophet ﷺ faces both practical and cognitive deviations. This paper critically examines the Qur’anic and Hadith-based dimensions of respect for the Prophetﷺ and evaluates current Muslim practices, highlighting that the revival of proper prophetic etiquette is essential for intellectual balance, spiritual elevation, and the authentic realization of the essence of Islam. Keywords: Etiquette of the Prophet, Respect and Reverence, Islamic Ethics, Contemporary Muslim Practices